Effect of increasing the fat content but not the energy load of a meal on gastro-oesophageal reflux and lower oesophageal sphincter motor function. Issue 3 (1st March 1998) - Penagini, R; Mangano, M; Bianchi, P A
Abstract : Background —Although fatty foods are commonly considered detrimental in patients with reflux disease, no objective data exist that substantiate this belief. Aims —To investigate the effect of fat on gastro-oesophageal reflux and lower oesophageal sphincter (LOS) motor activity. Subjects —Thirteen healthy subjects and 14 patients with reflux disease. Methods —Oesophageal pH, LOS, and oesophageal pressures were recorded for 180 minutes after a high fat (52% fat) and a balanced (24% fat) meal (both 3.18 MJ) on two different occasions. Eight controls and seven patients were studied in the recumbent position and the others in the sitting position. Results —The percentage of time at pH less than 4 and the rate of reflux episodes were higher (p<0.01) in the patients than in the healthy subjects (mean 14.1% versus 1.7% and 4.4/h versus 0.8/h respectively), as was the percentage of transient LOS relaxations associated with reflux (62% versus 32%, p<0.01). The high fat meal did not increase the rate of reflux episodes nor exposure to oesophageal acid in either group regardless of body posture.The rate of transient LOS relaxations, their association with reflux, and basal LOS pressure were also unaffected. Conclusions —Increasing fat intake does not affect gastro-oesophageal reflux or oesophagogastric competence for at least three hours after a meal.